Akad Salam dan Relevansi Pemikiran Abu Hanifah dalam Transaksi Modern - Ghani Achmad Barokah; Faujan Adhipratama Arasyid; Dede Maman Fathurahman; Lina Marlina (STIKes Ibnu Sina Ajibarang, 2025)
Islamic economics has been practiced since the time of the Prophet Muhammad. However, at that time until several centuries later there was no special classification of disciplines for economics, causing several Muslim works to be lost. The role of scholars in this case is very influential in the sustainability of Islamic economics both in terms of theory and implementation. This journal aims to review the thoughts of Islamic economics from scholars, one of whom is Imam Abu Hanifah. By matching whether Imam Abu Hanifah's thoughts are still relevant and can be applied in the modern era. The method used is research with the study method used is library research. Where researchers use books, journals, periodical articles, yerbooks, bulletins, annual reviews, historical records, magazines, and newspapers as the main subject of their study. The results of this study are that Imam Abu Hanifah's thoughts on the salam contract are still relevant and can be implemented in the modern era. although not all sales and purchase contracts can use the salam contract method because there are several conditions that must be met in this contract.